Diet Quality, Child Health, and Food Policies in Developing Countries - Bhargava, Alok (World Bank Group, Washington, DC, 2014)
Although the importance of diet quality for improving child health is widely recognized, the roles of environmental factors and the absorption of nutrients for children's physical growth and morbidity have not been adequately integrated into a policy framework. Moreover, nutrient intakes gradually affect child health, so it is helpful to use alternative tools to evaluate short-term interventions versus long-term food policies. This article emphasizes the role of diet quality reflected in the intake of nutrients such as protein, calcium, and iron for children's physical growth. Vitamins A and C are important for reducing morbidity. Children's growth and morbidity affect their cognitive development, which is critical for the future supply of skilled labor and economic growth. Evidence on these issues from countries such as Bangladesh, India, Kenya, the Philippines, and Tanzania is summarized. The supply of nutritious foods is appraised from the viewpoint of improving diet quality. Finally, the roles of educational campaigns and indirect taxes on unhealthy processed foods consumed by the affluent in developing countries are discussed.